LINC00936/microRNA-221-3p Regulates Tumor Progression in Ovarian Cancer by Interacting with LAMA3 - Shu, Chenggan; Wang, Weiwei; Wu, Lipei; Qi, Chunrun; Yan, Wenhui; Lu, Wenying; Tian, Jiale; Shang, Anquan (Recent Patents on Anti-Cancer Drug Discovery, 2023)
Background: Ovarian cancer remains a leading cause of mortality in women. It is known that long non-coding RNA (lncRNA) controls various biological processes and pathogenesis of many diseases, including cancers. This study aimed to determine whether LINC00936 and microRNA-221-3p (miR-221-3p) influence the laminin alpha 3 chain gene (LAMA3) in the development of ovarian cancer. Methods: The expressions of LINC00936, miR-221-3p, and LAMA3 in ovarian cancer and adjacent tissues were assessed. Furthermore, ovarian cancer cells were transfected with vectors with overexpressed LINC00936, miR-221-3p mimic, miR-221-3p inhibitor, and si-LAMA3 to elucidate their functions in ovarian cancer cell proliferation, migration, invasion, angiogenesis, and tumorigenesis. The binding relationship between LINC00936 and miR-221-3p and the relationship between miR-221-3p and LAMA3 were verified to explore the mechanism of action of LINC00936 in ovarian cancer. LINC00936 binds to miR-221-3p as a ceRNA and regulates the expression of LAMA3. Results: LINC00936 and LAMA3 were poorly expressed, while miR-221-3p was highly expressed in ovarian cancer tissues. Over-expression of LINC00936 contributed to decreasing miR- 221-3p expression and increasing LAMA3 expression. LINC00936 overexpression or miR-221- 3p silencing downregulated the levels of PCNA, MMP-2, MMP-9, and VEGF and decreased cell proliferation, migration, invasion, angiogenesis, and ovarian cancer tumorigenesis. Conclusion: Collectively, overexpression of LINC00936 suppressed the development of ovarian cancer by competitively binding to miR-221-3p and controlling LAMA3 expression. These results could serve as a novel theoretical base for the treatment of ovarian cancer.
Keywords: Ovarian cancer